The impact of monetary policy variables inflation in Algeria: standard study using self regression time gaps - مراد, صاولي; الياس, بومعراف; فارس, عبد الرحماني (Journal of Economics and Administrative Sciences, 2018)
In the past years, the Algerian Economy has witnessed various monetary developments characterized by different monetary and banking reforms aimed by monetary authorities to achieve monetary stability and driving overall growth. It should be noted that there is evidence to initiate fundamental changes on the basis of which new monetary, financing and banking policy mechanisms must be formulated in Algeria by enhancing the pursuit of reforming the monetary system, in order to improve monetary and economic indicators.                The study aims to clarify the economic stability policies forms adopted by several countries in order to combat the economic structural imbalances. Based on monetary policy instruments and the fact that the monetary policy represents a side of general economic policy, it requires a high degree of coordination between its instruments. So, a strong conviction have been generated by monetary policymakers that price stability should be the long-term goal of monetary policy and monetary aggregates that have not been effective for long time In fighting inflation, prompting a new monetary policy approach focusing directly on reducing inflation.                There are indications of fundamental changes in the vision on which the monetary policy mechanisms were formulated in Algeria, in order to ensure the safety of the financial system, Inflation has become an important economic indicator for the measurement of economic growth rates in Algeria, and it requires to the monetary authorities to research its determinants and address its causes. As far as it becomes an economic problem as much as it has a quantitative methods for assessing it and provide mathematical methods to measure it and explain its causes and treatment, and showed how monetary policy instruments are integrated to face the inflationary pressures. For that, the study concluded to estimate a long-term relationship between several national monetary policy variables using the ARDL model.